Evaluation of Different Nutrient Management Practices in Yield of Different Rice Cultivars in Lamjung District of Nepal - Ranabhat, S.; Amgain, L.P. (International Journal of Applied Sciences and Biotechnology, 2016)
A field experiment was conducted on farmer’s field at two sites of Lamjung district of Nepal viz. Bhotewodar and Sundarbazaar to evaluate the performance of two commonly grown rice varieties viz US-382(hybrid) and Ramdhan (improved) under two nutrient management practices [Nutrient Expert®(NE) rice model recommendation, and government recommendation(GR)].Four replicates of four treatments were arranged in randomized completely block design. Rice varieties responded differently under the different nutrient management practices in terms of plant height, grains per panicle, sterility%, panicle weight, grain yield at 15% moisture, straw yield and harvesting index. The highest grain yield was obtained from NE field of US-382 variety which was followed by GR for US-382, NE for Ramdhan and GR for Ramdhan variety. NE based practices for US-382 variety produced higher biological yield as compared to GR. NE estimated attainable rice yield provided by the software compared with actual rice yield from the trials in farmer’s field and NE-based fertilizer recommendations proved the validity in reaching the yield targets estimated by the software. The observed rice yields recorded in the trials were higher than the NE estimated attainable yields, so NE recommendation for US-382 variety was found better over GR. Int J Appl Sci Biotechnol, Vol 4(2): 223-227